Description sheet to seed regulatory framework analysis - McEwan, M.; Spielman, David J. (International Potato Center, 2021)
Purpose: to provide actionable evidence on and investment options to accelerate seed system and market development in countries where vegetatively propagated crops (VPCs) are important to food security and agricultural development.